One Health Concept with Emphasis on Zoonoses - M.G.Jayathangaraj; M.Raman (The Indian Veterinary Journal, 2024)
There are many diseases that are communicable from animals to human beings esp. the wild fauna.  When population of any one species increases due to multifaceted etiological factors, there may be an increase in the incidences of few zoonotic diseases, which cause more potential risks to the humans, in reality. Outbreaks of diseases have been documented in many incidences, esp. the diseases like Nipah viral infections.  Japanese encephalitis, leptospirosis, Erysipeleas infections, Zerka viral infections etc. are the examples of such diseases related to the zoonotic pathogens affecting both man and animals. All such diseases need not be expected to reveal significant clinical symptoms apparently but the potentials related to the general health status, performance and reproduction related aspects may get frequently affected to a greater extent. Working together of both veterinary and medical communities was emphasized in order to maintain one health policy and close dependency between animal and human health is a vital factor to be taken into account when one health policy is to be achieved, successfully.